We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
408
1
avatar

R=-9+3a

 May 9, 2016
 #1
avatar+173 
-1

Let's solve for a.

r=−9+3a

Step 1: Flip the equation.

3a−9=r

Step 2: Add 9 to both sides.

3a−9+9=r+9

3a=r+9

Step 3: Divide both sides by 3.

3a

3

=

r+9

3

a=

1

3

r+3

 May 9, 2016

6 Online Users

avatar